Begonia leipingensis (Begoniaceae), a new compound-leaved species with unique petiolule pattern from Guangxi of China - Li, Chun; Yang, Li-Hua; Tian, Dai-Ke; Chen, Yue; Wu, Rui-Juan; Fu, Nai-Feng (Phytotaxa, 2016)
Begonia leipingensis D. K. Tian, L. H. Yang & C. Li (2n = 30), a new species in Begonia sect. Coelocentrum from the limestone area of Guangxi, China. B. leipingensisis is easily distinguished from any other compound-leaved species in Begonia by its large variation in petiolule number and its unique spirally-arranged petiolule pattern, which has never been seen in Begoniaceae before and rarely seen even in other angiosperm taxa. Besides having non-overlapping flowering periods, it is clearly different from B. fangii, the most morphologically similar species in the same section and with the same chromosome number. In addition to its unique petiolule pattern, B. leipingensis has longer abaxial wings, shorter internodes, and usually larger leaves, leaflets and habit. Molecular phylogenetic analysis showed that B. leipingensis formed an independent lineage belonging to Sect. Coelocentrum. Morphological and phylogenetic evidence strongly supports this species as a new taxon in Sect. Coelocentrum of Begonia. B. leipingensis was assessed to be critically endangered based on criterion outlined by IUCN Red List Categories and Criteria.